Analisis Pengembangan Produk Ekspor Woven Earth Craft - Ais Mariya Ulva; R. Yuniardi Rusdianto (Universitas Katolik Widya Karya Malang, 2024)
Exports are goods and services produced in one country and sold to buyers in another country. The biggest contributing factor to Gross Domestic Product is exports.